Eu3+ ion distribution in oxyfluoride glass nanocomposites - Antuzevics, Andris; Krieke, Guna; Pavlovska, Elina; Rogulis, Uldis (Elsevier, 2019)
Assessment of activator distribution in lanthanide doped nanocomposites is an important and challenging task. Oxyfluoride glass ceramics have been chosen as a model system to characterize incorporation efficiency of Eu3+ ions in CaF2 nanocrystals using a combination of X-ray diffraction (XRD) and electron paramagnetic resonance (EPR) techniques. Lattice constant changes induced by size mismatch of Eu3+ and Ca2+ ions have been used to evaluate Eu3+ content in CaF2. The distortion of CaF2 lattice due to incorporation of europium ions can be detected from EPR investigations via Gd3+ paramagnetic probe spectra. It is shown that ratio of different symmetry CaF2:Gd3+ centres and linewidth of EPR transitions can be used to monitor europium content in the crystalline phase of glass ceramics. ---- / / / ---- This is the preprint version of the following article: A. Antuzevics, G. Krieke, E. Pavlovska, U. Rogulis, Eu3+ ion distribution in oxyfluoride glass nanocomposites, Journal of Non-Crystalline Solids, 522, 119548 (2019), DOI https://doi.org/10.1016/j.jnoncrysol.2019.119548, which has been published in final form at https://www.sciencedirect.com/science/article/abs/pii/S0022309319304193. This article may be used for non-commercial purposes in accordance with Elsevier Terms and Conditions for Sharing and Self-Archiving. This work is licensed under a CC BY-NC-ND 4.0 license.
The authors are grateful to Dr. Andris Fedotovs for photography of the samples. This research is funded by the Latvian Council of Science, project “Novel transparent nanocomposite oxyfluoride materials for optical applications”, project No. LZP-2018/1-0335.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Transparent oxyfluoride glass ceramics; Activator distribution; Optical spectroscopy; X-ray diffraction; Electron paramagnetic resonance